Программа основного магистерского курса “История и теория социологии” - Поляруш, Б. (Социология: теория, методы, маркетинг, 2001)
The mandatory course programme on “History and theory of sociology” for MA students at the Ivan Franko National University of L’viv. Topic 1. Development of theoretical sociology. Topic 2. The sociological analysis of culture. Topic 3. Society as a social system. Topic 4. Social institutes and organizations. Topic 5. Social communites. Topic 6. The personality in a system of social relations. Topic 7. Social interaction. Topic 8. Social changes and problems of a globalization.